2010
DOI: 10.1002/adfm.201000169
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide‐Derived Carbons for Polar Analyte Separations

Abstract: Highly mesoporous (Brunauer–Emmett–Teller surface area, SBET > 200 m2 g−1; mesopore volume > 1 cm3 g−1) carbonaceous materials are prepared in a truly sustainable manner, from the naturally occurring polysaccharide alginic acid. This approach yields large mesoporous materials (pore diameter > 14 nm) significantly without the use of a template or carbonization catalyst. The direct thermal decomposition of mesoporous forms of the acidic polysaccharide allows for an extremely flexible material preparation strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 54 publications
1
86
0
1
Order By: Relevance
“…These types of stationary phases were found to be particularly efficient at separating the sugars, for example, glucose (monosaccharide), sucrose (disaccharide), and raffinose (trisaccharide). The resultant ion chromatograms had good peak shape and near-baseline resolution (White et al, 2010a).…”
Section: Starbon ò Applicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…These types of stationary phases were found to be particularly efficient at separating the sugars, for example, glucose (monosaccharide), sucrose (disaccharide), and raffinose (trisaccharide). The resultant ion chromatograms had good peak shape and near-baseline resolution (White et al, 2010a).…”
Section: Starbon ò Applicationsmentioning
confidence: 95%
“…These foams were formed after displacing water within an aquagel matrix with ethanol and then drying to form a low-density mesoporous solid (a type of microcellular foam). Continued research within this area has found that this technology can be applied to other polysaccharide and nonpolysaccharide sources such as alginic acid (White et al, 2010a), pectin (White et al, 2010b), and poly(vinyl alcohol) (PVA) (Hunt et al, 2009). The understanding of why some polymers and not others can form these types of porous solids has not yet been definitively concluded, but the general rationale is that if the linear chain fragment of polymers can form a helical type arrangement, then porous solids may result.…”
Section: Porous Polysaccharidesmentioning
confidence: 99%
“…The final product has a variable structure, stability, and chemistry that ranges from starch-like amorphous carbon to commercially available activated carbons [87]. The three-step carbonization process yields materials with high surface areas ranging from 150 m 2 /g to approximately 600 m Depending on the synthesis procedure, these biomass-derived carbons have a wide range of applications that include the separation of polar analytes [91], CO2 capture [92], and heterogeneous catalysis [93][94][95][96][97][98][99][100]. Sulfonated starbons have catalyzed the esterification of succinic, fumaric, itaconic and levulinic acids to their respective diesters in the presence of water [93,94,96].…”
Section: Starch Carbonization (Starbon ® )mentioning
confidence: 99%
“…These samples represent respectively materials prepared using the same pyrolysis temperature as White et al [11] and the pyrolysis temperature more recently favoured for the preparation of Starbon ® material [14].…”
Section: Introductionmentioning
confidence: 99%
“…has been shown to be effective in the LC separation of low mass carbohydrates [11], with retention comparable to that on a commercial PGC column [12]. Synthesis of alginic acidderived Starbon ® involves the expansion of an alginic acid hydrogel in water, followed by solvent exchange with ethanol and supercritical CO 2 drying to produce an aerogel precursor, which is then subjected to pyrolysis at up to 1000 o C under an inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%